Tafhim al-Quran: An Analytical Study of Abu al-A la Mawdudis Approach to the Understanding of Ayat al-Ahkam - Sarker, Md Masum (IIUC Studies, 2016)
The aim of this paper is to study the approach of Abu al-A la Mawdudi to the understanding of Ayat al- Ahkam based on his tremendous scholarly work i.e. Tafhim al-Quran. The research has relied on inductive, objective and analytic methods in order to accumulate and study various Ayat al-Ahkam, and to evaluate objectively the position of Tafhim. Mawdudi emphasizes Ijtihad for extracting verdicts from Ayat al-Ahkam. In his view, al- Qur'an is not against the juristic disagreements as long as they do not contradict with the principles of Islam, and nor do they lead to disputes. Furthermore, many a time he has compared and gave preponderance among the views of jurists while in some cases he presented the views only. In addition, his juristic views were free from any doctrinal bigotry and were strongly supported by convincing evidences including previously revealed scriptures. Sometimes he has criticized the Western laaws in order to establish the superiority of Quranic legislations and rejected the misinterpretation of the Ayat al-Ahkam by indisputable strong evidences. IIUC Studies Vol.10 & 11 December 2014: 231-262